2018
DOI: 10.1055/s-0038-1646932
|View full text |Cite|
|
Sign up to set email alerts
|

Gender Disparity between Absolute versus Relative Size of Condylar Chondral Defects: An MRI Analysis

Abstract: Surgical repair of articular cartilage defects in the knee currently utilizes surgical algorithms based on absolute defect size. These algorithms, which have not been validated, are currently utilized not only by surgeons but also by insurance carriers for justification of reimbursement policy. However, current algorithms do not account for morphological differences between individual patients and defect size relative to condylar dimension. We hypothesized that a significant difference in relative defect size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…14,33,43,59 Additionally, morphologic differences existed among patients of various races. 38 Berman et al 5 verified these differences through an MRI study of 220 skeletally mature patients (110 males and 110 females) and demonstrated significant relative defect size differences among patients, as a chondral defect measuring 10 mm may represent as little as 24.29% of a condyle in some males as opposed to 77.46% in smaller females.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14,33,43,59 Additionally, morphologic differences existed among patients of various races. 38 Berman et al 5 verified these differences through an MRI study of 220 skeletally mature patients (110 males and 110 females) and demonstrated significant relative defect size differences among patients, as a chondral defect measuring 10 mm may represent as little as 24.29% of a condyle in some males as opposed to 77.46% in smaller females.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, current treatment algorithms utilize only the absolute defect size and do not account for the size and morphological differences of the affected joint among patients. Berman et al 5 recently demonstrated that there was up to a 3-cm condylar width difference and as much as a 53.17% difference in relative defect size for a 10-mm defect between sexes. When this is taken into consideration of several previous studies showing that larger chondral defect sizes result in worsening knee biomechanics, elevated adjacent rim peak forces, and even increased local chondral catabolic activity, relative defect size may be a valuable measure to determine potential treatment options.…”
mentioning
confidence: 99%
“… Were the results well-described? Quality summary Kaspiris et al [ 14 ] 2 Berman et al [ 20 ] 2 Nemeth 2017 2 Antony et al [ 21 ] 2 Kumar et al [ 16 ] 2 Pachowsky et al [ 23 ] …”
Section: Resultsunclassified
“…Moreover, Berman et al [ 20 ] discovered gender-based morphological variations in the architecture of femoral condyles, even in patients with the same height. A stratified study of patient height and medial/lateral condylar width revealed a significant difference in condylar widths for each stratum.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the measurement and analysis protocol previously described, the primary measurements of interest in this study were the mean width of the medial and lateral femoral trochlea in males versus females. 24 Secondary values derived from these measurements that were analyzed include the maximum difference in trochlear width between males and females, the range of trochlear widths among the entire sample, the proportion of total donor cartilage a hypothetical graft plug would represent, and the mean height and weight for male and female patients.…”
Section: Resultsmentioning
confidence: 99%